SISTEM INFORMASI E-COMMERCE BAJU RAJUT MENGGUNAKAN METODE B2C - Marlinda, Linda; Rianto, Harsih (Jurnal Pilar Nusa Mandiri, 2012)
The technology of integrated information stored information in the form of documents with information that can be viewed on the monitor screen that consists of words, numbers, diagrams, videos, sounds, and images. Information technology can be utilized for marketing the much-loved crafts community. Particular crafts of knitting materials such as bags, shirts, bags HP, tablecloths and various other products requiring precise marketing tools and accurate that can be published and marketed throughout Indonesia. By working on competent parties especially in the world of IT (Information Technology) can provide to contribute to helping women artisans craft of knitting materials. So that is exactly what factors ultimately marketing information systems is made.